Women in Utilities : A Driving Force for Workforce Modernization – A Case Study of Three Utilities in the Danube Region - World Bank Group (World Bank, Washington, DC, 2019)
Diversity at the top of an organization can lead to better decision making and governance, and gender-inclusive companies—including utilities—can better reflect the needs of a diverse set of consumers. In the Danube region, utilities often face a predominantly male and sometimes aging workforce. However, gender gaps in tertiary education are closing, including programs in science, technology, engineering, and mathematics. For the water sector, creating an environment with equal opportunities for men and women at all levels of responsibility should therefore be an integral part of every utility's modernization process. Beginning in 2017, the Danube Water Program and the World Bank Global Water Security and Sanitation Partnership collaborated with three pioneering utilities in the Danube region to take a closer look at gender equality in their workplace: Brasov Regional Water Utility in Romania, the Prishtina Regional Water Utility in Kosovo, and the Tirana Water Utility in Albania. The assessment focused on four areas that determine success in gender equality, and results show that although all utilities have their individual strengths and weaknesses, there is wide scope for improvement toward optimal performance through human resource practices that foster a more gender-inclusive workforce.